GIS and spatial analysis in veterinary science - Durr, P. A. (Peter A.); Gatrell, Anthony C. (CABI Pub., 2004)
"This book is the first to review the subject of geographical information systems (including remote sensing) and spatial analysis as applied to veterinary science. Topics covered include the application of GIS to epidemic disease response, to companion animal epidemiology and to the management of wildlife diseases. It also covers issues such as parallels with human health and spatial statistics in the biomedical sciences. The book will be of significant interest to researchers in veterinary epidemiology and geography."--Jacket